Apivectoring: Harnessing pollinators for sustainable crop protection and pollination - SHARMA, AARUSHI; SHARMA, DEVIKA (Journal of Biological Control, 2024)
Apivectoring, or Pollinator Biocontrol Vector Technology, employs bees to distribute biological control agents, offering a sustainable solution for managing plant diseases and insect pests while enhancing crop yield and quality. The most commonly used vectors in apivectoring are honey bees and bumble bees, though there’s potential to explore other pollinator species. Commercial dispensers like BeeTreat Dispenser®, BVT Inoculum Dispenser® and Flying Doctors® have been developed in countries like Finland, Belgium, and Canada, respectively. Though initially pioneered in North America, Australia, and Europe, this method is now being evaluated in India. The technology is a promising alternative to chemical pest control, reducing pesticide usage and ensuring crop pollination, although challenges remain in regions deprived of local rearing and/or research facilities.